S79 Localised hypoxia enhances neutrophil extravasation and activation in interstitial lung disease. (15th November 2017) - Khawaja, AA; Sahota, J; Pericleous, C; Ripoll, VM; Chong, DLW; Azzopardi, G; Thomas, LW; Booth, HL; Groves, AM; Ashcroft, M; Giles, I; Porter, JC
Abstract : Background: Neutrophilic inflammation is common in various diseases and may contribute to the pathophysiology of interstitial lung disease (ILD), however the underlying mechanism are not fully understood. Localised tissue hypoxia is often accompanied with inflammation, which may alter cellular responses to drive immunopathology. Hypothesis: We propose that hypoxia modulates neutrophil functions including integrin activation, neutrophil extravasation and neutrophil extracellular trap (NET) release that may contribute to pulmonary damage in ILD Methods: Pulmonary hypoxia was assessed using both fluoromisonidazole (FMISO)-PET scanning of ILD patients and immunohistochemical HIF-1a staining in ILD and control lung sections. To examine the effects of hypoxia, isolated neutrophils were cultured under hypoxia (1% oxygen) or normoxia (21% oxygen) prior to experimentation. Neutrophil integrin expression was evaluated using flow cytometry. Neutrophil adhesion and trans-endothelial migration were measured using fluorescence-based assays. Reactive oxygen species (ROS) production was measured using an enzymatic assay to assess hydrogen peroxide (H2 O2 ) generation. NETosis was measured using a novel capture ELISA. Bronchoalveolar lavage (BAL) were obtained from ILD or control patients and assessed for NETs. Results: FMISO-PET scans indicated localised hypoxia in fibrotic regions in ILD patients. Hypoxia was also determined in lung sections, which demonstrated positive HIF-1a in ILD but not control lung sections. ILD-BAL had significantly greater levels of NETS compared to control (p=0.0039). Hypoxia did not affect b1 integrin expression, however increased surface expression of the aM and aX subunits (p=0.0001 and 0.0179 respectively). Unstimulated, PMA- and LPS-stimulated neutrophil adhesion to both ?resting and activated endothelial monolayers were enhanced under?hypoxia. Neutrophil trans-endothelial migration, across both resting and activated endothelial cells, was also greater in hypoxia (p<0.05). Interestingly, whilst ROS generation was not affected by?hypoxia, both spontaneous and PMA-induced NETosis were increased under hypoxic conditions (p<0.05 and 0.001 respectively). Conclusions: We have demonstrated that localised hypoxia is a feature of the ILD lung. Moreover, elevated NETs were found in ILD-BAL, suggesting a role for aberrant neutrophil activation in ILD pathology. Hypoxia increased neutrophil b2 integrin expression, adhesion to endothelial monolayers, trans-endothelial migration and NETosis. Further work is underway to investigate the signalling pathways underlying neutrophil activation in ILD.